Of Mosquitoes and Men: The Basis of Animal and Human Rights - Doomen, Jasper (Philosophy & theology, 2016)
This article discusses whether animal rights may be defended from a natural rights or an ethical perspective. Both options fail. The same analysis applies in the case of humankind. ‘Humankind’ does not bring with it the acknowledgement of rights, nor does a focus on what is arguably characteristic of humankind, reason. Reason is decisive, though, in another respect: the fact that reasonable beings can claim and lay down rights. It does not follow from this that animals should have no rights, since human beings may be motivated to constitute such rights, while this provides the most solid basis for them.